Odpowiedzi

2009-11-14T12:36:26+01:00
A) (3x+7y)(2x-2xy) = 6x² - 6x²y + 14xy - 14xy²
b) (4a-2b)(3a+2b) = 12a² + 8ab - 6ab - 3b² = 12a² + 2ab - 3b²
c) (7x-2y)² = 49x² - 28xy + 4y²
d) (5a+3b)² = 25a² + 30ab + 9b²
e) (9x+4y)(7y-2x) = 63xy - 18x² + 28y² - 8xy = 28y² - 18x² + 55xy
2009-11-14T12:37:13+01:00
A) 6x²+6x²y+14xy-14xy²
b) 12a²+8ab-6ab-4b²=12a²+2ab-4b²=2(6a²+ab-2b²)

Dalej nie wiem soryy
2009-11-14T12:43:34+01:00
A)(3x+7y)(2x-2xy)=6x²-6x²y+14xy²-14xy²
b)(4a-2b)(3a+2b)= 12a²+8ab-6ab-4b²=12a²+2ab-4b²
c)(7x-2y)²= 49x²-24xy+4y²(wzory skróconego mnożenia)
d)(5a+3b)²=25a²+30ab+9b²(to samo)
e)(9x+4y)(7y-2x) =63xy-18x²+28y²-8xy=-18x²+28y²+55x²